Suppression of Platelet Aggregation by Bordetella pertussis Adenylate Cyclase Toxin - Iwaki, Masaaki (American Society for Microbiology, 1999)
The effect of Bordetella pertussis adenylate cyclase toxin (ACT) on platelet aggregation was investigated. This cell-invasive adenylate cyclase completely suppressed ADP (10 μM)-induced aggregation of rabbit platelets at 3 μg/ml and strongly suppressed thrombin (0.2 U/ml)-induced aggregation at 10 μg/ml. The suppression was accompanied by marked increase in platelet intracellular cyclic AMP (cAMP) content and was diminished by the anti-ACT monoclonal antibody B7E11. A catalytically inactive point mutant of ACT did not show the suppressive effect. Since an increase of cAMP content is a known cause of platelet dysfunction, these results indicate that the observed platelet inactivation was due to the catalytic activity of ACT through increase of intracellular cAMP.